Role of sialylated glycans in cancer progression : sialyl-Tn and sialyl-Lewisx - Carrascal, Mylène Adelaide do Rosário (2020)
ABSTRACT: Glycosylation is a posttranslational modification of proteins and lipids, able to regulate a diversity of biological processes. Changes in glycosylation result in alterations in these processes and have been associated with cancer development and progression. One of the most commonly reported change in cancer glycosylation is an increased sialylation, which have been associated with malignant features and poor prognosis. Since sialic acid is a terminal sugar, it is normally involved in numerous biological processes, such as cellular recognition, cell adhesion and cell-to-cell signaling. In cancer cells, the increase of sialylated glycans seems to affect several cell-cell mechanisms, promoting cancer survival. However, the role of sialylated glycans in cancer progression is still poorly understood. In this thesis, we aimed to clarify the role of two specific sialylated glycans, sialyl-Tn (STn) and sialyl-Lewis X/A (sLeX/A), which are typically overexpressed in cancer. We aimed to understand whether they contribute to cancer progression, in particular in the recognition of tumor cells by immune cells and in the process of invasion and metastasis. In the immune recognition of cancer, dendritic cells (DCs) play a unique and decisive role in tumor immunity, being capable of activating antigen-specific cytotoxic T cells. However, to efficiently prime T cells, DCs have to undergo maturation, which is usually prevented by the tumor environment through many immunosuppressive strategies. STn glycan is expressed by more than 80% of human carcinomas and is associated with many malignant features, such as invasiveness and proliferation. Clinically, STn has been used as a target for cancer therapeutic strategies; however, STn-based vaccines tested in clinical trials have not been as efficient as expected, highlighting the low immunogenicity of STn. Here, we showed that STn expression in bladder cancer tissues is associated with an immature DCs phenotype. Using bladder cancer cells overexpressing ST6GalNAc1, which leads to STn expression, we demonstrated that DCs in contact with STn+ cancer cells have a more immature profile, expressing less MHC-II antigen presenting molecules and co-stimulatory molecules (e.g. CD80 and CD86), and producing less proinflammatory cytokines, in comparison with DCs with STn- cancer cells. Although DCs were able to uptake more STn+ apoptotic cancer cells, it led to a reduced ability to activate T cells. These findings showed that the expression of STn glycan in cancer cells hinder the immune response by inducing a more tolerogenic profile in DCs. In addition, we also verified that antibodies against STn, or its protein carriers (CD44 and MUC1), seem to revert this immature phenotype in DCs, suggesting that antibodies can be used to overcome the low immunogenicity of STn+ cancer cells. Regarding the sLeX/A antigens, we focused in their role as E-selectin ligand in breast cancer, as an important step for cell migration. Both sLeX and sLeA are the most common glycan structure in the glycoconjugates (proteins or lipids) able to bind E-selectin, which is expressed upon inflammation on vascular endothelium and is crucial during the process of extravasation of cancer cells from the bloodstream to form new metastasis. In order to better understand the role of these glycans in cancer progression, in particular the mechanisms mediated by E-selectin ligands (sLeX/A) in breast cancer, we established new primary breast cancer cell cultures from invasive ductal cancer tissues, which preliminary results had shown to have higher expression of E-selectin ligands. To understand these mechanisms, we inhibited sLeX/A expression by using a fucosylation inhibitor, named 2-fluorofucose (2-FF), in breast cancer cells. In the cell line showing higher expression of E-selecting ligands, namely the CF1_T cell line, we proved that 2-FF inhibitor abrogated the expression of functional E-selectin ligands, as well as reduced the proliferation index and migration capacity of the cells. We also showed that CF1_T cells treated with 2-FF inhibitor expressed lower levels of growth factors and consequently, ERK1/2 and p38 signaling pathways were less activated than in untreated cells, suggesting that the expression of E-selectin ligands, such as sLeX/A, has a major impact on malignant features, such as cell signaling/proliferation, adhesion and migration, contributing to tumor progression. E-selectin engagement is not only dependent on the sLeX/A glycan structures but also on its carrier molecules, whose nature is still poorly known in breast cancer. The identification of these molecules may reveal potential novel targets in therapy to circumvent cancer progression. Here, through the characterization of the glycoconjugates decorated with sLeX/A expressed by CF1_T breast cancer cell line, we revealed that they were mainly N-glycosylated proteins. Their nature was identified by mass spectrometry after immunoprecipitation with E-selectin chimera. From those, CD44 and CD13 glycoproteins were confirmed, by western blot, as carriers of sLeX/A glycans. CD44 had already been identified as an E-selectin ligand in cancer; however, CD13 glycoprotein, although being associated to cancer, has never before been described as being able to bind E-selectin. While further studies are still necessary to elucidate the exact contribution of CD13, this study suggest this glycoprotein as a potential interesting target for novel anticancer therapy. Within breast cancer subtypes, the triple negative breast cancer (TNBC) has a more aggressive course and increased probability of distant recurrence. So far the expression of sLeX/A glycans and general E-selectin ligands in TNBC is unknown. To address this, we develop a staining protocol using E-selectin chimera by immunohistochemistry. Our results showed that E-selectin ligands, such as sLeX/A, expression is negatively correlated with the expression of CK5/6, which is a basal-like biomarker associated with better survival rate in TNBC patients. The relevance of this association of E-selectin ligands and CK5/6 expression in TNBC are still under investigation. Overall, our findings have contributed to elucidate the role of two sialylated glycans, STn and sLeX/A, in cancer progression. Specifically, the data reported here shed light into the putative role of STn in the immunological escape of tumor cells and explore the role of E-selectin ligands, mainly sLeX/A, on cancer ability to growth and develop metastasis, pointing out to novel potential therapeutic targets in cancer.